Persepsi Guru TK dan SD Terhadap Pelaksanaan Transisi PAUD ke SD yang Menyenagkan di Kota Gorontalo - Mutmainna Ts Bullah; Wenny Hulukati; Muhamad Zubaidi (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This study aims to understand teachers' perceptions of the implementation of a joyful transition from Early Childhood Education to elementary school, as well as to identify the obstacles in carrying out this transition. The research method employed descriptive quantitative. Data collection was conducted through questionnaires distributed to 20 respondents and interviews with 5 participants. The results showed the perception of kindergarten teachers in schools such as TK Pembina Kec. Kota Utara Kindergarten, TK Alkhairat Kindergarten, TK Al-Huda Kindergarten, TK Aisyiyah Bustanul Athfal VII Kindergarten, and TK Aster Kindergarten were categorized as "good" with 78%. Meanwhile, the perception of elementary school teachers in schools such as SD 59 Kota Timur Elementary School, SDN 94 Kota Utara Elementary School, SDN 97 Kota Utara Elementary School, SDN 75 Kota Tengah Elementary School, and SDN 88 Sipatana Elementary School was in the "very good" category with 83%. The results indicated that the participants provided positive responses regarding their perceptions of implementing the joyful transition from PAUD to elementary school.